Synthesis, characterisation and properties of bis(permethylindenyl) iron and tin complexes - Ransom, P; Arnold, T; Thompson, A; Buffet, J; O'Hare, D (Elsevier, 2014)
Neutral iron complex, (EBI∗)Fe (EBI∗ = ethylenebis(1-hexamethylindenyl)), and its cationic analogue, [(EBI∗)Fe](BF4), have been synthesised. Both rac- and meso-(EBI∗)Fe can be isolated but the isomeric distribution of the reaction products was found to be highly sensitive to the reaction conditions employed. The redox behaviour of rac-(EBI∗)Fe in solution has been studied by cyclic voltammetry, it shows a one-electron reversible oxidation at -0.7 V vs. (Cp)2Fe/(Cp)2Fe+. Chemical oxidation of (EBI∗)Fe with AgBF4 gives [(EBI∗)Fe](BF4). The molecular structures of rac-(EBI∗)Fe and meso-[(EBI∗)Fe](BF4) have been determined by single crystal X-ray structure analysis. (EBI∗)(SnMe3)2 was synthesised by the reaction of [(EBI∗)]Na2 with ClSnMe3 in THF. In solution, only two of the many possible isomers are observed by 1H NMR spectroscopy. Single crystals of (EBI∗)(SnMe3)2 were grown as pale, plates by the slow cooling to -78 °C of a saturated hexane solution of a mixture of the isomers. 1H NMR analysis of the crystals showed them to be the isomer with C-SnMe3 peaks at a chemical shift of - 0.27 ppm.